La violencia de género en varones en el Barrio la Dolorosa Parroquia de San Pablo de Atenas 2022. - Verdezoto Galeas, Ivon Cristina (2024)
For a long time, violence against men is generally understood as gender violence, in most cases they refrain from reporting it out of shame, because there is a legal vacuum, and there are no exclusive institutions for the protection of men, The objective of this research is to know the causes and effects of gender violence in men in the Barrio la Dolorosa San Pablo in Atenas. It seeks to analyze and find out why men are violated and in turn find methods to stop this problem, taking into account that it is as normal as violence against women. The study is focused on gender violence as a problem of a social nature with events that violate human rights, which should not be taken as an isolated event, but rather, clear policies must be designed that lead to the application of effective measures. protection for men, as well as the creation of assistance and care services. Regarding the methodology, the quantitative approach was applied, for which the information collection mechanism and instrument were in-depth surveys. Surveys are defined as a conversation that is proposed with a specific purpose (Díaz, Torruco and Martinez, 2013). In conclusion, in many Latin American countries, judicial systems are going through moments of crisis and face serious problems due to the lack of legislation on violence against the male gender. Keywords: Violence, Gender, Masculinity, victimization, human rights